14 The Statutes at Large of Pennsylvania from 1682 to 1801, at 456 (1909) - (:unkn) unknown (My University, 1793)
"[A]ll young men under the age of twenty-one years, and all servants purchased bona fide and for a valuable consideration," had to enroll in the militia. But "during such minority or servitude," they were exempt from training and from fines for not having the requisite equipment. The exception did not apply "in cases of rebellion, or an actual or threatened invasion of this or any of the neighboring states."
Keywords: MILITIAS